Prison employment and its conflict with therapeutic and counselling programmes: The experiences of Czech prison personnel - Mertl, Jiří (European journal of criminology, 2023)
The study investigates a specific issue in the Czech prison system: the conflict between prison employment and therapeutic/counselling programmes offered. Drawing on 55 semi-structured interviews with specialized prison personnel from 10 Czech prisons, I argue that prison employment is disproportionately prioritized over the programmes, which undermines and, in some cases, makes it impossible for the personnel to work with inmates on rehabilitation. Since the Czech Prison Service itself declares that most inmates have serious problems involving psychological traumas, drug abuse, and housing insecurity, it would be beneficial to prioritize rehabilitation programmes and then try to employ inmates. The conflict also contributes to an unsuccessful re-entry/resettlement process, which is regarded as a major problem in the Czech prison system and society.